Controlled attenuation parameters to assess liver steatosis in obese patients with polycystic ovary syndrome - Wang, Dongxu; Nan, Nan; Bing, Hao; He, Bing (Frontiers in Endocrinology, 2023)
Objectives: This study was performed to investigate the changes and influencing factors of liver controlled attenuation parameter (CAP) in obese patients with polycystic ovary syndrome (PCOS), and to determine the prevalence and risk factors of nonalcoholic fatty liver disease (NAFLD) in PCOS patients with obesity.Methods: Forty-one PCOS patients with obesity and twenty age-and body mass index (BMI)matched control women without PCOS were enrolled in this study. General data, body composition, biochemical parameters, sex hormones, and liver CAP in the two groups were collected and compared. Liver CAP was measured using transient elastography.Results: NAFLD was more common in the Obese PCOS group than in the control group (75.61% vs. 45.00%, P=0.018). Compared to the control group, the obese PCOS group showed apparent increases in alanine transaminase (ALT), aspartate transaminase (AST), CAP, triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), totle testosterone (TT), free androgen index (FAI), fasting insulin (FIns), and homeostasis model assessment-insulin resistance (HOMA-IR), along with lower high-density lipoprotein cholesterol (HDL-C) and sex hormone binding globulin (SHBG) levels. In addition, as shown by Spearman analysis, liver CAP in PCOS patients with obesity had a positive correlation with ALT, AST, TG, TT, FAI, FIns, and HOMA-IR, and a negative correlation with SHBG. Logistic regression analysis showed that TG, TT, FIns, and HOMA-IR were risk factors for NAFLD, while TT was an independent risk factor for NAFLD in PCOS patients with obesity.PCOS patients with obesity had a significantly higher prevalence of NAFLD. Furthermore, in PCOS patients with obesity, liver CAP was associated with disorders of lipid metabolism, insulin resistance, and hyperandrogenemia, with elevated testosterone levels being an independent risk factor for NAFLD in PCOS patients with obesity.